Prepubertal exposure to bisphenol-A induces ERα upregulation and hyperplasia in adult gerbil female prostate - Campos, Mônica S. [UNESP]; Galvão, André L. V.; Rodríguez, Daniel A. O.; Biancardi, Manoel F.; Marques, Mara R.; Vilamaior, Patrícia S. L. [UNESP]; Santos, Fernanda C. A.; Taboga, Sebastião R. [UNESP] (International Journal of Experimental Pathology © 2015 International Journal of Experimental Pathology., 2015)
Prostate physiology is highly dependent on oestrogenic and androgenic homeostasis. Interferences in this equilibrium, especially in early periods of life, may disrupt the prostate and increase the susceptibility to the development of diseases with ageing. Taking this into account, and considering the increase of environmental chemicals with endocrine-disrupting potential such as bisphenol-A (BPA), this study aimed to evaluate the prostates of adult female gerbils exposed to BPA and BPA plus testosterone from pubertal to adult periods. Morphological, stereological and chemical analyses revealed that long-term BPA exposure, even in environmental dosages, increases the proliferative status of the prostate, increases the number of ERα-positive stromal cells and elicits the development of prostatic hyperplasia in adult female gerbils. Moreover, we also observed that the association with testosterone did not increase the proliferative status of the gland, which shows that low levels of BPA are enough to cause an oestrogenic disruption of the prostate in young adults. This evidence suggests that this oestrogenic endocrine disruptor may increase the susceptibility to prostatic disorders with ageing.
Keywords: Bisphenol-a; Endocrine-disrupting chemicals; Female prostate; Gerbil; Oestrogen receptor-alpha